2004
DOI: 10.1177/030089160409000214
|View full text |Cite
|
Sign up to set email alerts
|

Low Expression of P63 and P73 in Osteosarcoma

Abstract: Our data suggest that low expression of p63 and p73 is relatively common in osteosarcomas and might contribute to their molecular pathogenesis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 34 publications
0
16
0
Order By: Relevance
“…P73 can induce apoptosis and cell cycle arrest by binding to p53 response gene or trans activating p53 response gene (25). p73 has low expression in OS, and the triggering of p73 dependent apoptosis in OS is controlled by the E2Fs-pRb2/p130 complex (26,27). However, no interaction between miR-663b and TP73 in OS cells has been reported previously.…”
Section: Discussionmentioning
confidence: 95%
“…P73 can induce apoptosis and cell cycle arrest by binding to p53 response gene or trans activating p53 response gene (25). p73 has low expression in OS, and the triggering of p73 dependent apoptosis in OS is controlled by the E2Fs-pRb2/p130 complex (26,27). However, no interaction between miR-663b and TP73 in OS cells has been reported previously.…”
Section: Discussionmentioning
confidence: 95%
“…The presence of p63 in giant cell tumor of bone was not entirely unexpected as it has been detected in osteosarcomas and in bone marrow cells. 19,20 However in those studies as RNA from the entire tissue was examined it is not known if p63 was preferentially expressed in any particular cell type. The mechanism(s) leading to p63 protein overexpression in giant cell tumor of bone is not known.…”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge, in tumors of bone and soft tissue p63 expression has only been described in osteosarcoma, where it is postulated to contribute to the development of these tumors. 19 Bone and soft tissue neoplasms containing multinucleated giant cells represent a heterogeneous group of benign and malignant tumors. Differentiation among these tumors based on morphology alone can be challenging, particularly in instances of limited sampling, such as with needle-core biopsies.…”
mentioning
confidence: 99%
“…They found that alpha smooth actin is strongly and diffusely expressed in mononuclear stromal cells in nonossifying fibroma and brown tumour of hyperparathyroidism. In all giant cell tumours of bone tested (19), more than 10 % of mononuclear stromal cells (MSC) showed antialpha smooth actin immunoreactivity and in 42 % of cases more than 50 % of the cells stained. In contrast, in all ABC and RG, most tumours had between 10 and 50 % of stained cells, while 65 % of CB had no more than 10 % of alpha smooth actin positive MSC.…”
Section: Utility Of P63 Ihc For a Diagnosis Of Benign Giant Cell-richmentioning
confidence: 99%